Experimentally Induced Open Pneumothorax in Horses - Canola, Paulo A. [UNESP]; Valadão, Carlos A.A. [UNESP]; Canola, Júlio C. [UNESP]; Flôres, Fabíola N.; Lopes, Maristela C.S. (My University, 2019)
The objective of this study was to evaluate clinical and cardiovascular parameters and pleural and intra-abdominal pressures of horses after experimentally induced unilateral open pneumothorax. Prospective, experimental study—animals: seven healthy adult horses, 4 females and 3 males. Left hemithorax thoracotomy was carried out to create an open pneumothorax for 60 minutes. Pleural pressure (Ppl) was directly obtained at the midpoint of the left eighth intercostal space before thoracotomy. Esophageal pressure (Pes), arterial blood gas analysis, left ventricular function, and ultrasonographic assessment of pneumothorax extent/resolution were performed at the baseline, and 5, 10, 15, 30, 45, and 60 minutes after thoracotomy, and on the first, second, third, fifth, and seventh days postoperatively. Intra-abdominal pressure was only recorded while the pneumothorax was present. There was moderate correlation (Spearman's rs = 0.404; R2 = 0.8; P < .00001; Bland-Altman bias = −2.59; s.d. = 2.11) between Pes and Ppl. Esophageal pressure increased (P < .05) after open pneumothorax until the fifth day postoperatively. Partial pressure of oxygen in arterial blood reduced (P < .05) until the third day postoperatively when it returned to the baseline. No significant variations in PaCO2, pH in arterial blood, and in left ventricular function were appreciated. The extent of the pneumothorax was assessed by thoracic ultrasonography. Esophageal pressure, in association with blood gas analysis and thoracic ultrasonography, could be used to aid diagnosis of pneumothorax in horses. Horses tolerate open pneumothorax, with minimum cardiovascular impairment, even without aspiration of free air from within pleural space to restore thoracic wall integrity.
Keywords: Arterial blood gas analysis; Equine; Esophageal pressure; Thoracic trauma; Thoracic ultrasonography